Identification et aptitudes technologiques des bactéries lactiques du lait de chèvre - Otsmane Elhaou, Zahia (My University, 2016)
During our work, we proceeded to the characterization and identification of lactic acid isolates from goat milk from several regions of Algeria. After this, we studied some technology skills of some strains identified. Identification of 120 isolates lactic revealed a dominance of Leuconostoc’s kind in this milk, average 33%. After identification, we choose 12 strains for the technological capacities (including Leuconostoc). The results of the assessment of technological capabilities indicate that all strains have a good acidify power, proteolytic, texturing but low lipolytic power.
Keywords: Isolats; souches lactique; lait de chèvre; identification; aptitudes technologiques; Isolates; lactic strains; goat milk; technological capacities